Reciclaje de polietileno desde el enfoque del desarrollo sostenible para la producción de madera plástica y disminución del impacto ambiental en la ciudad de Latacunga - Moreano Sinchiguano, Fausto Javier (2021)
This work proposes a strategic plan for the production and commercialization of plastic wood promoting sustainable development in Latacunga city, directed towards companies of the construction and furniture sector, with the purpose of manufacturing and commercializing the product of derived demand, taking into account that there are countless materials in the market that supply vegetable wood; Thus, in the commercialization process, strategies must be applied to raise awareness among people so that they consume products with low environmental impact, and the manufacturer of final products is obliged to use this type of materials in order to increase sales to a greater degree. The financial analysis shows that the strategic plan is viable because the NPV is $ 753,498.96, allowing the company to invest in new assets. The profitability presented by the IRR is 48.49% and determines that the project is viable since the WACC is 14%. The project as a whole had a profitability of $1.95 and the time it will take the project to recover the initial investment will be 2 years, 2 months and 29 days.